Patient selection for mechanical thrombectomy in posterior circulation emergent large-vessel occlusion. Issue 3 (June 2018) - Raymond, Scott; Rost, Natalia Sana; Schaefer, Pamela Whitney; Leslie-Mazwi, Thabele; Hirsch, Joshua A; Gonzalez, Ramon Gilberto; Rabinov, James
Triage of posterior circulation stroke from emergent large-vessel occlusion (pc-ELVO) is challenging owing to the stuttering clinical course and potential for rapid decline. Growing clinical data support the use of mechanical thrombectomy in pc-ELVO, but there are limited data addressing the clinical and imaging criteria for patient selection. We present our triage algorithm used to select patients for endovascular therapy (EVT) in the setting of pc-ELVOS. We use a consecutive retrospective database from 2004 to 2016 to describe the practice patterns and prognostic factors for pc-ELVO patients treated using both medical and EVT. Patients with moderate to severe deficits (NIHSS > 10) did better when they received EVT ( p < 0.03), whereas patients with stable, mild deficits (NIHSS ≤ 10) did well (90% favorable outcome) regardless of treatment type. Roughly one-third of patients presenting with mild deficits deteriorated to moderate to severe deficits (NIHSS > 10), most of whom subsequently received EVT (9 of 12), with 56% favorable outcomes. Cerebellar and brainstem infarct volumes were independent imaging predictors of outcome. These results can be used to define triage criteria for use of EVT in pc-ELVO in future practice and clinical trials.